Understanding interactive technology in organizational settings: A focus on user experience - Andrei, Daniela; Flestea, A.; Guran, A.; Miclea, M. (IGI Global, 2015)
Despite the growing interest in holistic approaches capable to go beyond utilitarian perspectives in understanding users’ relationship with interactive technology, user experience remains largely ignored in organizational settings (Bargas-Avila & Hornbæk, 2011). Traditionally, technology use in organizations was seen as almost completely externally motivated by the need to perform certain tasks. But this is bound to change as complex interactive technologies are increasingly used by organizations and as research indicating the importance of work motivation for employees performance and well-being (Gagné & Deci, 2005) is starting to be considered in the field of interactive technology interaction (Harbich & Hassenzahl, 2008). As a result, this paper addresses the opportunities of applying a user experience approach in organizational settings by providing an overview of the existing research and insights into how important individual and contextual variables might be considered in order to better understand the way desired technology-related outcomes can be facilitated.